Hidradenitis suppurativa – biologic therapy and other available treatment options - Lipa, Katarzyna; Zając, Natalia; Witkowski, Grzegorz; Ciechanowicz, Piotr; Wiszniewski, Kacper; Szymańska, Elżbieta; Walecka, Irena (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2023)
Hidradenitis suppurativa (HS) is a chronic recurrent inflammatory skin disease that is characterized by painful, recurrent nodules and abscesses. The overall prevalence of HS is estimated to be 11 per 100,000 individuals in the United States and 4% of the world’s population. Women are 3 times more affected than men, especially patients between 18 and 29 years of age. Similarly to acne vulgaris, HS is primarily associated with follicular occlusion, which results from a number of biological processes, including follicular epithelial hyperplasia and hyperkeratinisation. There are numerous available treatment options for cutaneous lesions in the course of HS. A combination of conservative therapy and appropriate surgical treatment conducted by an experienced surgeon ensures the best possible clinical outcomes. Presently, biologic therapy is the most effective pharmacological treatment in patients with moderate to severe course of the disease. Numerous ongoing clinical trials provide hope for greater availability of new biologic therapy methods.